Perturbaciones reales sobre la Cuenta Corriente: Equilibrio parcial keynesiano vs. enfoque intertemporal de la cuenta corriente - Mariano Fernández (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
– The purpose of this paper is to contrast the Keynesian partial equilibrium framework of the Current Account with the modern intertemporal general equilibrium approach where the Current Account imbalances reflect, and act as a buffer, against both real and monetary shocks. The document will try to highlight the failure of the partial equilibrium approach and will analyze, in the face of different real shocks, how the outcome of the Current Account will be the mirror of the macroeconomic imbalance that caused it.
Keywords: E12; E32; E62; E58; F32; F41; 330; Cuenta Corriente; Deficit; Sustitucion intertemporal; estructuralismo; Shocks reales; Temporario; Permanente